Prenatal screening of cytogenetic anomalies – a Western Indian experience - Sheth, Frenny (BMC Pregnancy Childbirth, 2015)
BACKGROUND: Children born with congenital anomalies present a very high rate of perinatal death and neonatal mortality. Cytogenetic analysis is a convincing investigation along with clinical suspicion and biochemical screening tests. The current study was designed to characterize the prevalence and types of chromosomal abnormalities in high risk prenatal samples using different cytogenetic techniques. METHODS: This study was conducted on a total of 1,728 prenatal samples (1,324 amniotic fluids, 366 chorionic villi and 38 cord blood samples) from 1994 to 2014 at Institute of Human Genetics, Ahmedabad, India. Conventional karyotyping was conducted with GTG-banding. Molecular approaches were used (fluorescence in situ hybridization = FISH and/ or array-comparative genomic hybridization = aCGH) when indicated to detect karyotypic abnormalities. RESULTS: Abnormal karyotypes were detected in 125/1,728 (7.2%) cases. Trisomy 21 was the most common abnormality detected in 46 (2.7%) followed by trisomy 18 in 11 (0.6%) and trisomy 13 in 2 (0.1%) samples. Besides, structural abnormalities such as reciprocal and Robertsonian translocation were detected in 20 [1.2%] cases. Turner syndrome was diagnosed in seven (0.4%) cases; in six (0.34%) cases there was an inversion in the Y-chromosome. Heteromorphic variants were diagnosed in 22 (1.3%) cases. Finally, small supernumerary marker chromosomes (sSMC) were found in six (0.34%) cases. CONCLUSION: Conventional GTG-banding along with molecular cytogenetic techniques is useful in detecting genomic alterations and rearrangements. Comprehensive characterization of chromosomal rearrangements like sSMC has the potential to save potentially healthy fetuses from being terminated.